Fungi associated with invasive plant species in Cuba - Camino-Vilaró, Mayra; Castro-Hernández, Lázaro; Abreu-Herrera, Yudisleidys; Mena-Portales, Julio; Cantillo-Pérez, Taimy (Phytotaxa, 2019)
Several fungi use a wide range of plant species as hosts and others have high specificity for the host plant, invasive plants included. In this compilation, 676 fungal records associated to 102 species of invasive plants are recognized in Cuba, some of them are host specific and others are known from several hosts. Most of the fungal records are representatives of Ascomycota and also most of these records were found on/in leaves. The plant species Syzygium jambos, Bambusa vulgaris, Psidium guajava, Delonix regia, Citrus aurantium, Casuarina equisetifolia and Citrus × aurantiifolia are the ones with the highest numbers of associated fungi.